KUNCI SUKSES USAHA KEDAI KOPI (STUDI KASUS - AMING COFFEE) - Sigit Normagiat; Muhammad Syarif Syaifudin (Badan Penelitian dan Pengembangan Provinsi Kalimantan Barat, 2023)
Coffee shops are often used to stay in touch, relax after work, discuss business, or chat. This drinking coffee culture has shifted from a way of recreation and relaxation to a way of life for the people. The development of the coffee shop business is growing rapidly at this time, including Aming Coffee, which was initially only on a local scale but has now managed to expand its market share to a national scale. One interesting and important thing to research was related to the factors that influence Aming Coffee to have a good image in the eyes of customers. This study used the observation method of site conditions and visitors. Questionnaires and semi-structured interviews were conducted to obtain data on visitor perceptions of service quality (X1), price (X2), product (X3), location (X4), and purchase decisions (Y). Furthermore, multiple multilinear regression analysis was performed using the MS Excel 365 data analysis tool to determine the factors influencing purchasing decisions. The observation results show an increase in Aming Coffee visits in the afternoon. The total recorded visits fluctuated at the beginning and middle of the week and peaked at the weekend. Based on multiple multilinear regression analyses, the results show that the factors of service quality (X1), price (X2), product (X3), and location (X4) together have a significant effect on the consumer's decision to drink coffee at Aming Coffee (Y). So, the quality of service, price, product, and location all balance the consumer's decision to drink coffee at Aming Coffee.